2019
DOI: 10.1017/wet.2019.32
|View full text |Cite
|
Sign up to set email alerts
|

Using energy requirements to compare the suitability of alternative methods for broadcast and site-specific weed control

Abstract: The widespread use of herbicides in cropping systems has led to the evolution of resistance in major weeds. The resultant loss of herbicide efficacy is compounded by a lack of new herbicide sites of action, driving demand for alternative weed control technologies. While there are many alternative methods for control, identifying the most appropriate method to pursue for commercial development has been hampered by the inability to compare techniques in a fair and equitable manner. Given that all currently avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 121 publications
0
33
0
1
Order By: Relevance
“…However, even reasonably objective effects can be difficult to compare. For example, Coleman et al, [166] found that many mechanical treatments use less energy than glyphosate per pass because of the energy needed to produce glyphosate. However, they could only estimate glyphosate energy consumption based on one old study since this information is considered a trade secret.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, even reasonably objective effects can be difficult to compare. For example, Coleman et al, [166] found that many mechanical treatments use less energy than glyphosate per pass because of the energy needed to produce glyphosate. However, they could only estimate glyphosate energy consumption based on one old study since this information is considered a trade secret.…”
Section: Discussionmentioning
confidence: 99%
“…This means that after a successful application, glyphosate will often not need to be applied as frequently as the tillage strategies, which may have to be applied annually or biennially. By some estimates, tillage treatments against annual weeds can have a lower overall energy cost than glyphosate [166], but for perennials like E. repens this is likely to be offset by the increased number and frequency of operations that are needed for control. One of the major arguments against tillage has been that it increases the risk of nutrient leaching and erosion, especially if conducted during periods of heavy rainfall, which is often the case in autumn.…”
Section: Control In the Intercrop Periodmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to directly target individual weeds provides the opportunity for the introduction and use of alternate weed-control technologies. One reason for the lack of development of these technologies is the unacceptably high energy (and hence, cost) requirements for effective weed control (Coleman et al 2019). The research of Coleman et al (2019), however, highlighted that the site-specific weed control approach that, due to the substantial energy and cost savings, creates the opportunity to develop alternative, nonchemical weed-control technologies for large-scale crop production systems.…”
Section: Introductionmentioning
confidence: 99%